Epigrafi medievali ruotate: due casi toscani del XII secolo - Frati, Marco (Studi e ricerche di storia dell'architettura, 2025)
In the ancient world, the exhibited turning of an epigraph upside down in relation to a previous text serves as a cancellation of the first meaning, without cutting the primitive link with it, its support and its context, especially in private inscriptions. In the Middle Ages, especially after the ‘Gregorian’ Reformation, the use of ancient materials became charged with further meanings, in an attempt to link the early Church to the present one. More rare and no less interesting is the re-use of dated and/or signed medieval plaques, inserted in slightly later phases of the same site, placed in pregnant locations of buildings (especially religious ones) and, therefore, resemantised. Two Tuscan case studies that are more or less well-known (Sant’Antimo in Val di Starcia and San Martino in Campo on Montalbano) and datable to around the 12th century help to trace the meaning of an operation that is anything but a damnatio memoriae. This contribution includes the edition of the epigraphs and their stratigraphic contextualization, in order to date their production and re-use; the reconstruction and reconsideration of the historical and architectural events that led to the overturning of the text; the comparison with other episodes of resemantisation of pre-existing inscriptions. The inscription of Sant’Antimo is the basis for the reconstruction of the church and renews the monastery’s alliance with the nobility; that of San Martino recalls the community’s resilience in reacting to the destruction caused by a natural disaster.